2023
DOI: 10.3389/fphar.2023.1288618
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus emblica: a comprehensive review of its phytochemical composition and pharmacological properties

Arya Tjipta Prananda,
Aminah Dalimunthe,
Urip Harahap
et al.

Abstract: Phyllanthus emblica Linn, a prominent member of the euphorbiaceae family, exhibits extensive distribution across a multitude of tropical and subtropical nations. Referred to as “Balakka” in Indonesia, this plant assumes various names across regions, such as “kimalaka,” “balakka,” “metengo,” “malaka,” and “kemloko” in North Sumatra, Ternate, Sundanese, and Java respectively. Phyllanthus emblica thrives in tropical locales like Indonesia, Malaysia, and Thailand, while also making its presence felt in subtropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…In this study, the phylogenetic tree of gene families was constructed for seven species, i.e., B. ramiflora , R. communis , M. esculenta , H. brasiliensis , J. curcas , P. euphratica , and A. thaliana . The results revealed that B. ramiflora grouped into two clades with species from the Euphorbiaceae family, consistent with previous phylogenetic studies 45 , 46 . The divergence time between B. ramiflora and Euphorbiaceae species indicated a close relationship between B. ramiflora and P. euphratica within the Euphorbiaceae family as sister groups.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the phylogenetic tree of gene families was constructed for seven species, i.e., B. ramiflora , R. communis , M. esculenta , H. brasiliensis , J. curcas , P. euphratica , and A. thaliana . The results revealed that B. ramiflora grouped into two clades with species from the Euphorbiaceae family, consistent with previous phylogenetic studies 45 , 46 . The divergence time between B. ramiflora and Euphorbiaceae species indicated a close relationship between B. ramiflora and P. euphratica within the Euphorbiaceae family as sister groups.…”
Section: Discussionsupporting
confidence: 91%
“…The total antioxidant capacity estimated in aqueous extract was 75.10% and ethanol extract content was 86.06%. Hence it is evident that the bark consists of high antioxidant content in the ethanolic sample, the P. emblica extract in rats showed a dose-dependent decrease in levels of oxidative damage 29,30 .…”
Section: Quantification Of Total Phenolmentioning
confidence: 99%
“…The supernatant was bought from a pre-weighed vial and allowed to evaporate. Then the purified extract from preparative TLC was evaluated for antibacterial efficacy against selected bacterial pathogens using the well diffusion method 25 .…”
Section: Preparative Tlcmentioning
confidence: 99%
See 1 more Smart Citation
“…Amla is itself known for its beneficial properties like it is high in Vitamin -C .It helps in healing scurvy . It also has many other medicinal properties such as antibacterial, antifungal, antioxidant properties [12][13][14][15][16] . Amla fruit is consumed in Indian diet in forms of pickles, juices , candies etc.…”
mentioning
confidence: 99%